2014
DOI: 10.1101/gad.238105.114
|View full text |Cite
|
Sign up to set email alerts
|

PRDE-1 is a nuclear factor essential for the biogenesis of Ruby motif-dependent piRNAs in C. elegans

Abstract: Piwi-interacting RNAs (piRNA) are small regulatory RNAs with essential roles in maintaining genome integrity in animals and protists. Most Caenorhabditis elegans piRNAs are transcribed from two genomic clusters that likely contain thousands of individual transcription units; however, their biogenesis is not understood. Here we identify and characterize prde-1 (piRNA silencing-defective) as the first essential C. elegans piRNA biogenesis gene. Analysis of prde-1 provides the first direct evidence that piRNA pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 53 publications
6
130
0
1
Order By: Relevance
“…There has been some debate regarding the overall length of the precursors: Cecere et al have detected a >60 nt capped transcript using 5′ RACE, whereas Gu et al detected shorter 26 nt putative precursor species by small RNA sequencing (Cecere et al, 2012;Gu et al, 2012b). We and others have recently refined this finding showing that it is indeed short species of 28 or 29 nt that are made from most piRNA loci (Goh et al, 2014;Weick et al, 2014).…”
Section: Piwi Proteins and Pirna Biogenesis In C Elegansmentioning
confidence: 84%
See 2 more Smart Citations
“…There has been some debate regarding the overall length of the precursors: Cecere et al have detected a >60 nt capped transcript using 5′ RACE, whereas Gu et al detected shorter 26 nt putative precursor species by small RNA sequencing (Cecere et al, 2012;Gu et al, 2012b). We and others have recently refined this finding showing that it is indeed short species of 28 or 29 nt that are made from most piRNA loci (Goh et al, 2014;Weick et al, 2014).…”
Section: Piwi Proteins and Pirna Biogenesis In C Elegansmentioning
confidence: 84%
“…Our laboratory has identified piRNA defective 1 (PRDE-1) as a novel factor that is essential for the generation of Ruby-motif dependent piRNA precursors and accumulates in pachytene germ cell nuclei on chromosome IV. PRDE-1 is either involved in generating these precursors by direct or indirect interaction with the motif or may stabilise the precursors once they have been transcribed from the motif (Weick et al, 2014). Furthermore, using an RNAi based genome-wide screen, the Hannon lab has identified several other factors required for C. elegans piRNA biogenesis, which they collectively refer to as TOFUs for 'twenty-one U fouled up' (Goh et al, 2014).…”
Section: Piwi Proteins and Pirna Biogenesis In C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, most of piRNA biogenesis factors identified in other animals, including the endonuclease Zucchini/MitoPLD, are not conserved in worms. In this issue of Genes & Development, three groups (de Albuquerue et al 2014;Goh et al 2014;Weick et al 2014) report on their discoveries of novel factors that are involved in the production of 21U-RNAs in C. elegans. Goh et al (2014) performed an RNAi screen covering >80% of annotated C. elegans protein-coding genes and identified 22 genes that affect mature 21U-RNA levels (named TOFUs).…”
Section: Twenty-one-u Fouled Ups (Tofus)mentioning
confidence: 99%
“…piRNA silencing defective 1 (prde-1) Weick et al (2014) also conducted EMS mutagenesis screening using a 21U-RNA sensor and identified PRDE-1. PRDE-1 has a protein kinase-like domain, but amino acid residues critical for ATP binding in the kinase domain are not conserved.…”
Section: Twenty-one-u Fouled Ups (Tofus)mentioning
confidence: 99%